51st AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2013
DOI: 10.2514/6.2013-245
|View full text |Cite
|
Sign up to set email alerts
|

Study of a Swept Wing with Leading-Edge Ice Using a Wake Survey Technique

Abstract: The aerodynamics of swept wings with leading-edge ice is very complex and not fully understood. Previous swept wing icing studies have only provided force balance measurements and/or qualitative flow visualization. In order to more fully understand the complex aerodynamics it is necessary to understand how the ice influences the drag breakdown and the spanwise distributions of lift and drag. This paper utilizes 5-hole probe wake surveys and a far-field analysis to decompose the drag into profile and induced dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The results indicate that, for a fixed CL, the ice shape results in a significant increase in the profile drag, whereas the induced drag is unaffected. In the surface oilfiow, not shown here, it was observed that the size of the region of separated flow, relative to the local chord, increased as the tip was approached [6,15]. The flow visualizations of Diebold and Bragg [15] and Diebold et al [6] showed a leading-edge vortex behind the ice shape that grows with angle o f attack.…”
Section: Resultsmentioning
confidence: 56%
See 4 more Smart Citations
“…The results indicate that, for a fixed CL, the ice shape results in a significant increase in the profile drag, whereas the induced drag is unaffected. In the surface oilfiow, not shown here, it was observed that the size of the region of separated flow, relative to the local chord, increased as the tip was approached [6,15]. The flow visualizations of Diebold and Bragg [15] and Diebold et al [6] showed a leading-edge vortex behind the ice shape that grows with angle o f attack.…”
Section: Resultsmentioning
confidence: 56%
“…The accuracy of the wake-survey technique was assessed by comparing the lift and drag measured by the force balance to that calculated from the wake. Despite the underprediction in drag, Diebold and Bragg [15] showed that the drag curve measured by the wake survey closely followed the drag curve measured by the balance. Due to the small size of the model relative to the tunnel cross section, the standard wall corrections to the force balance measurements were negligible and did not affect the observed trends.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations